Influence of Cd2+ Ions Substitution on the Magnetic Properties of Ni-Cd Ferrites - V.S.В Bushkova (Журнал нано- та електронної фізики)
The polycrystalline of Ni-Cd ferrites were prepared by the technology sol-gel with participation of auto-combustion and sintered at temperature 1573В K in air. Low field hysteresis measurement was carried out at room temperature at frequency of 200В Hz and at the field range 1600-16000В A/m. The increase of Cd2+ ions yields the increase of specific saturation magnetization Пѓs and magnetic moment mexp up to xВ пЂЅВ 0.3 then decrease thereafter. The NeelвЂ™s two sublattice model can be applied to the sample up to xВ пЂЅВ 0.3. The composition dependence of the specific saturation magnetization and magnetic moment for 0.4В в‰¤В xВ в‰¤В 0.6 were explained on the basis of the existence of Yafet-Kittel angles on the B-site spins. The temperature variation of the initial permeability Ојi of these samples was carried out from 300 to 900В K. The initial permeability increases with increasing Cd content up to xВ пЂЅВ 0.3 after that it decreases. It was found that Curie temperature Tc decreases from 831 to 697В K.